Obstructive sleep apnea: the ‘noisy’ killer - Asha'ari, Zamzil Amin (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
Obstructive sleep apnea (OSA) is an upper airway disorder characterized by multiple interruptions of breathing during sleep manifested mainly as apnea or hypopnea. It is a common disorder worldwide. This is an editorial article discussion on why we should not treat OSA lightly as it has huge potential for cardiovascular mortality among its sufferers.